Regression Model in Transitional Geological Environment For Calculation Farming and Production of Oil Palm Dominant Factor in Indragiri Hilir Riau Province - Heriyanto Heriyanto; Detri Karya; Tiggi Choanji; Asrol Asrol; Djaimi Bakce; Elinur Elinur (UIR PRESS, 2019)
Palm oil commodity is plantation sub-sector commodity which can increase the income of farmers and communities, providers of raw material processing industries that create added value. Cultivated by smallholders self consists of land area, peatlands tidal, coastal peatlands and coastal lands. Differences typology of this land will contribute to the different productions. Generally, this study aimed to analyze the factors of production and farming oil palm, according to the typology of land Specifically aimed to analyze the production and cultivation of oil palm as well as the dominant factor affecting the production Kalapa smallholders' according to the typology of the land and to formulate policy implications of oil palm development patterns of the people in Indragiri Hilir in Riau province. To answer this research analyzed with descriptive statistics and build a multiple regression model with dummy variables Ordinary Least Square method (OLS). Memperlihatan research results that palm oil production and farming on land typology highest compared with tidal peat, peat coast, and coastal lands. Oil palm farming income on a non-pattern land typology best compared with other lands (peat tides, coastal peatlands, and coastal land). The dominant factor affecting the production of palm oil in Indragiri Hilir is the amount of fertilizer, labor, plant age, herbicides, and soil typology dummy land. Policy Implications development of oil palm plantation in Indragiri Hilir in order to increase production, productivity and farm income oil palm can be through the construction of roads production, provision of means of production and palm oil processing industry to shorten the distance and shorten the time of transport that TBS of oil palm plantations to the factory. Furthermore, the use of fertilizers, labor and land typology is very responsive to TBS production. Therefore, in the farming of oil palm cultivation should follow the recommended technical.